The Implementation of Hygiene Practices by Makeup Artists in Respecting Clients' Health Rights - Komang Trisna Widayanti; Ida Bagus Gede Fajar Manuaba (Indonesian Journal of Global Health Research, 2025)
Hygiene in the practice of makeup artists (MUAs) is a crucial aspect in Introduction: Ensuring the health and safety of clients. Violations of hygiene principles can increase the risk of skin infections, irritation, and disease transmission. This study aims to identify the implementation of hygiene standards practiced by MUAs and how these practices reflect respect for clients' health rights. This study used a descriptive qualitative approach. This study employed purposive sampling to select informants, a technique that involves selecting samples from the population based on the researcher's objectives and specific criteria. Data were collected through in-depth interviews with 10 professional MUAs and direct observation of their work practices. The data was collected by a questionnaire as its research instrument, which has been validated through a validity test conducted by an expert. Data were analyzed using thematic analysis techniques to identify patterns, trends, and practices that either reflect or violate hygiene principles. The results show that most MUAs were aware of the importance of hygiene; however, shortcomings remain in practices such as the use of unsterilized tools and makeup products being applied to multiple clients without disinfection. Four key themes were identified in this study: Factors Hindering Hygiene Implementation, The Relationship Between Hygiene and Clients' Health Rights, The Importance of Professionalization and Certification, and Implications of Professional Ethics. As hygiene awareness continues to grow globally—especially after the COVID-19 pandemic—there is an urgent need to improve practices in beauty services. In Bali, a top wedding destination, the stakes are even higher.